Research and contributions on a proposal to digitize funding activities of political parties and electoral campaigns in the Permanent Electoral Authority - Dragomir, Adrian-Viorel (Eximia, 2021)
Start The financing of political parties and election campaigns is a strategic issue for representatives of Romanian political organizations and the Permanent Electoral Authority (PEA). As a matter of intense debate in the public sphere in the past few years, the financing of political parties and election campaigns have become more important in the context of Romania’s long-term supervision by international agencies responsible for the fight against corruption. n this regard, the PEA strives to harmonize legislation with international standards for financing of political parties and election campaigns, and develop methods for controlling income and expenditures used for election activities, including here, the current work and campaigns of political organizations The specific work during the period shows that it is one of the institutions actively involved in the improvement of constituencies through digitization and innovation, and is in line with international recommendations in this field.